Search for a Standard of Proof in the Lithuanian Civil Procedure - Nekrošius, Vytautas; Bartkus, Jurgis (Teisė, 2024)
The article analyses the issues related to the standard of proof in the Lithuanian civil procedure. The study reveals that the social school of the civil procedure, on which the Code of Civil Procedure of the Republic of Lithuania is based, and the objective of establishing the substantive truth justify the application of the intime conviction standard in Lithuanian civil proceedings. The first part of the article analyses the historical sources of the Lithuanian civil procedure law which lead to the conclusion that, since the 19th century, the Lithuanian civil procedure has followed the ideas based on the social civil procedure school. The second part reveals that the concept of substantive truth, which means that the Court is fully or almost fully satisfied as to the correctness of the decision to be given in a case, has the closest connection with the social civil procedure school. This notion of truth determines a specific standard of proof, i.e., the application of the intime conviction standard. In the third part, by taking into account the social school of the civil procedure, the purpose of substantive truth and the provisions of the Lithuanian Code of Civil Procedure, it is concluded that the standard of intime conviction must be applied in Lithuanian civil proceedings. The fourth part reveals the Case Law of the Supreme Court of Lithuania concerning the standard of proof and its developments.